PENGARUH LITERASI KEUANGAN DAN AKSESIBILITAS TERHADAP KEPUTUSAN PENGGUNAAN TRANSAKSI DIGITAL OLEH UMKM PENGOLAHAN IKAN DI KOTA BENGKULU - Rince Novita Yulianda; Gita Mulyasari; Nola Windirah; Emlan Fauzi (Universitas Mataram, 2026)
Fish-processing MSMEs in Bengkulu City face increasing pressure to adapt to digital transactions within business payment systems characterized by high transaction intensity and rapid product turnover. This study aims to analyze the level of financial literacy and accessibility and to examine their effects on the decision to use digital transactions. A quantitative approach was employed through a survey of 100 fish-processing MSME actors in Bengkulu City. Data were collected using structured questionnaires and analyzed using descriptive statistics and Structural Equation Modeling based on Partial Least Squares. The results show that financial literacy is in the moderately high category with an average TCR score of 60.25 percent, while accessibility is also in the moderately high category with an average score of 66.26 percent. The financial management skills indicator recorded the lowest score among all indicators, indicating a gap between financial understanding and the practical implementation of financial administration. Structural analysis reveals that financial literacy has a positive and significant effect on the decision to use digital transactions, with a path coefficient of 0.526 and a t-value of 9.030, while accessibility also has a positive and significant effect with a path coefficient of 0.433 and a t-value of 6.990. Financial literacy is proven to have a more dominant influence than accessibility, indicating that readiness in financial understanding and financial management capability is the primary driver of digital transaction adoption among fish-processing MSMEs in Bengkulu City. The study implies the importance of strengthening practice-based financial literacy and providing simple digital payment systems that align with the characteristics of MSME businesses.